Detection of the cassava bacterial blight pathogen, Xanthomonas axonopodis pv. manihotis, by polymerase chain reaction - Verdier, Valerie M.; Mosquera Cifuentes, Gloria Maria; Assigbétsé, K. (Scientific Societies, 1998)
Cassava bacterial blight, caused by Xanthomonas axonopodis pv. manihotis, is of significant concern wherever cassava is grown. The movement of infected, asymptomatic stems is a major means of pathogen dispersal. A reliable and sensitive diagnostic procedure is necessary for the safe movement of cassava planting material. We used a cloned and sequenced pathogenicity gene of X. axonopodis pv. manihotis to develop a polymerase chain reaction (PCR) test for this pathogen. A set of primers directed the amplification of an 898-bp fragment in all 107 pathogenic strains of X. axonopodis pv. manihotis tested. PCR products were not observed when genomic DNA was tested for 27 strains of other xanthomonads, for saprophytic bacteria, or for five nonpathogenic strains of X. axonopodis pv. manihotis. The primers worked well for pathogen detection in direct PCR assays of X. axonopodis pv. manihotis colonies grown on liquid medium and in PCR assays of extracts from leaf and stem lesions. The minimum number of cells that could be detected from cassava stem and leaf lesions was 3 × 102 to 104 CFU/ml. The PCR assays proved to be relativyel sensitive and could become very useful in detecting the pathogen in cassava planting material.